Challenges for Baby Boomers Generation Teachers in Implementing the Industrial Revolution 4.0 Curriculum - Rosida Kerin Meirani; Astri Nabila; Diah Ayu Prabandari (Pelopor Publikasi Akademika, 2022)
The industrial revolution 4.0 is the technological era. In the world of education, technology is the key to success. Then the industrial revolution 4.0 curriculum emerged that included technology as its development. However, not all teachers are proficient in operating technology. The baby boomer generation is the generation that is considered the most difficult to adapt to technology because it was born in an era before technology so that the curriculum is a challenge. The purpose of this study is to find out the challenges of baby boomer teachers in implementing the 4.0 industrial revolution curriculum and their solutions. The research approach used is descriptive qualitative with literature study method. The challenges faced by these baby boomers are technology itself, motivation, and energy. Meanwhile, the solution to these challenges comes from the government, namely in the form of teacher certification and required competency training. From the school side, it is in the form of capacity building and providing motivation. And researchers also contribute solutions in the form of peer collaboration.